Note-Talking for consecutive interpreting: A short course. Second edition - Andrew Gillies
The basics step by step: Introduction; speech analysis; recognzing; the beginning; links; verticality and hierarchies of values; symbols; noting less; what to note. Fine tuning: clauses; rules of abbreviation; verbs; the recall line; uses of the margin; more on links; coparisons;... The back of the book.